Right-to-left-shunts in patients scheduled for neurosurgical intervention in semi-sitting position: a literature review based on two case scenarios - Nikolić, Marina; Eisner, Christoph; Neumann, Jan-Oliver; Haux-Nettesheim, Daniel; Krieg, Sandro; Wielpütz, Mark Oliver; Weigand, Markus A.; Tochtermann, Ursula; Fischer, Dania (BMC anesthesiology, 2024)
Neurosurgery performed in the semi-sitting position provides advantages for certain procedures. However, this approach is associated with potential complications, particularly venous air embolism. Due to typically negative venous pressure at the wound site, air can be drawn into the veins. This risk is especially high in patients presenting with an intra- or extracardiac right-to-left-shunt. Transoesophageal echocardiography can be used to detect a patent foramen ovale or other possible pulmonary-systemic shunt before placing the patient in the sitting position.
Gesehen am 26.03.2025